THE DEVELOPMENT OF E-GOVERNMENT IN INDONESIA SEEN THROUGH THE PRACTICAL PERSPECTIVE - Endang Amalia; Wisnu Azi Firdaus; Lis Sakhatun; Mohd Haizam Saudi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Starting with government issued a national policy and strategy development of e-government through Presidential Instruction No. 3 year of 2003, every ministry in Indonesia should have a website. However, the development of e-government continues to increase along with technological developments and societal needs for information and services efficiently and effectively. The development of e-government will involve a variety of factors that have contributed to the creation of a public service. All these factors need to be designed from scratch through a planning process in order to produce a development program of e-government that can be applied starting from the factor of leadership (leadership), human resources, organization and management systems, good communication, hardware, software, budget (funds), and others that must be incorporated into an integrated planning scenario, holistic, gradual, realistic and measurable. Through this research for the development of e-government in Indonesia in terms of a practical perspective is divided into two parts: the back office section and the front office section, which are both still in the stages of the process towards E-Government. The results of this research suggests that the government’s strategy have to be realized at least 85% of the entire strategies that has been formulated especially improvements through infrastructures, organizations and users.